2009
DOI: 10.1063/1.3073945
|View full text |Cite
|
Sign up to set email alerts
|

The secondary electron emission yield of muscovite mica: Charging kinetics and current density effects

Abstract: Using a dedicated Scanning Electron Microscope (SEM), operating in the spot mode, the charging properties of muscovite mica have been studied in the energy range 100-8000 eV. The intrinsic yield curve σ 0 (E), representing the variation of the yield of the uncharged material with the energy E, has been established: the maximum value of the yield is 3.92 at E = 300 eV and the two crossovers corresponding to σ 0 (E) = 1 are respectively at energies E I < 100 eV and E II = 4850 eV. At a given energy and under a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
(50 reference statements)
2
12
0
Order By: Relevance
“…This is achieved by alternating short electron pulses where r < 1 when the sample is positively charged and where r > 1 when the sample is negatively charged. [17][18][19] Note that the "as received" ceramics are usually charged before being exposed to electron beams and may in some cases exhibit a surface potential of tens to hundreds of volts (positive or negative). For instance, a positive surface potential of 67 V was measured on the BN-SiO 2 sample, whereas a negative surface potential of À49 V was measured on Al 2 O 3 .…”
Section: Methodsmentioning
confidence: 99%
“…This is achieved by alternating short electron pulses where r < 1 when the sample is positively charged and where r > 1 when the sample is negatively charged. [17][18][19] Note that the "as received" ceramics are usually charged before being exposed to electron beams and may in some cases exhibit a surface potential of tens to hundreds of volts (positive or negative). For instance, a positive surface potential of 67 V was measured on the BN-SiO 2 sample, whereas a negative surface potential of À49 V was measured on Al 2 O 3 .…”
Section: Methodsmentioning
confidence: 99%
“…4,5 In essence and in the case of oxides, it has been shown that breakdown could be delayed by introducing impurities, whose nature and concentrations meet specific requirements, or by achieving a microstructure that favors to some degree the spreading of charges. [6][7][8][9][10][11][12] Indeed, it contributes to the improvement of component reliability of industrial devices, for instance in thin insulating systems as those used in plasma display panels, 13 spacecraft insulating, 14 alumina rf-window, 15 power electronic capacitors, 16 high-k materials of metal-oxidesemiconductor structures, 17 and field emission display spacers. [6][7][8][9][10][11][12] Indeed, it contributes to the improvement of component reliability of industrial devices, for instance in thin insulating systems as those used in plasma display panels, 13 spacecraft insulating, 14 alumina rf-window, 15 power electronic capacitors, 16 high-k materials of metal-oxidesemiconductor structures, 17 and field emission display spacers.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Therefore, the ability of insulators to keep the charges trapped ͑or conversely to spread them͒ controls their dielectric properties. 18 Experiments using electron irradiation [8][9][10][11][12][13][14][15][16][18][19][20][21] and simulation studies [21][22][23] have provided a coherent framework for comprehensive description of the evolution of the generated charges ͑i.e., the injected electrons and the charge carriers ͑electrons and holes͒ that have been produced during the slowing down process of the primary electrons within the irradiated zone͒. 18 Experiments using electron irradiation [8][9][10][11][12][13][14][15][16][18][19][20][21] and simulation studies [21][22][23] have provided a coherent framework for comprehensive description of the evolution of the generated charges ͑i.e., the injected electrons and the charge carriers ͑electrons and holes͒ that have been produced during the slowing down process of the primary electrons within the irradiated zone͒.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This decrease has been associated with a progressive accumulation of positive charges that are distributed over a depth of about the escape length of secondary electrons λ. As suggested, this could be assigned to recombination of electrons with holes (in this zone), which should be otherwise emitted (Cazaux, 1986) or to field effect (Blaise et al, 2009). The other important feature is indeed that during injection, a negative charge distribution develops in the vicinity of the penetration depth of primary electrons R p .…”
Section: The Charging Kineticmentioning
confidence: 99%